Homes away from home Jewish belonging in twentieth-century Berlin, Paris, and St. Petersburg - Wobick-Segev, Sarah (Stanford, California Stanford University Press, 2018)
A room of their own : friendship, fellowship and fraternity -- A place for love : autonomy, choice and partnership -- Room to grow : children, youth and informal education -- A space for Judaism : rites of passage and old-new Jewish holydays -- Rebuilding after the Shoah : the challenges of remembering and reconstruction
Literaturverzeichnis: Seite 245-274
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Jews -- Social life and customs -- 20th century -- Europe; Judaism and secularism -- History -- 20th century -- Europe; Community life -- History -- 20th century -- Europe; Public spaces -- History -- 20th century -- Europe; Individualism -- History -- 20th century -- Europe; Leisure -- History -- 20th century -- Europe; Community life; Individualism; Jews -- Social life and customs; Judaism and secularism; Leisure; Public spaces -- Europe; Jews -- Europe -- Social life and customs -- 20th century; Judaism and secularism -- Europe -- History -- 20th century; Community life -- Europe -- History -- 20th century; Public spaces -- Europe -- History -- 20th century; Individualism -- Europe -- History -- 20th century; Leisure -- Europe -- History -- 20th century; Jews -- Germany -- Berlin; Jews -- France -- Paris; Jews -- Russia (Federation) -- Saint Petersburg; Jews -- Europe -- Social life and customs; Jews; Jews ; Social life and customs; Public spaces; Alltag; Gesellschaftsleben; Identität; Juden; Öffentlichkeit; Juifs ; Europe ; Moeurs et coutumes ; 20e siècle; Espaces publics ; Europe ; 20e siècle; Juifs ; Berlin (Allemagne); Juifs ; Paris (France); Juifs ; Saint-Pétersbourg (Russie ; région); History; Russia (Federation) ; Saint Petersburg; Germany ; Berlin; France ; Paris; Europe; Berlin; Europa; Paris; Sankt Petersburg